Treaties and acts of Congress relating to the Panama Canal : annotated 1921 / [compiled and annotated by J.J. McGuigan, under direction of the Governor, the Panama Canal]. - United States. (Tufts University. Tisch Library., 2017)
1 online resource; Includes supplements Nos. 1-20 issued from 1922 to 1934 and which continue the pagination of the base volume (p. 259-1054).; Tisch Outsourced Digitization 2017-10-02